A Systematic Literature Review on School Literacy Movement - Istiqomah (Universitas Negeri Jakarta, 2025)
Background The School Literacy Movement (SLM) has gained increasing attention as a strategic initiative to improve students’ literacy skills across various educational levels. This movement responds to global and national concerns about declining reading habits, comprehension skills, and critical thinking among students. Various studies have explored its implementation, challenges, and outcomes; however, a comprehensive synthesis of existing literature is needed to map the current state of research and identify gaps. Purpose This study aims to systematically review and synthesize research findings related to the School Literacy Movement, focusing on its objectives, implementation strategies, outcomes, and the challenges encountered. Design/method/approach This research adopts a systematic literature review (SLR) with databases such as Scopus, Web of Science, ERIC, and Google Scholar were searched for peer-reviewed articles published between 2020 and 2024. Results The review identified a total of 42 relevant studies. Findings show that the SLM has been implemented with varying degrees of success depending on contextual factors such as school leadership, teacher training, student engagement, and availability of resources. Most studies reported improvements in reading interest and comprehension; however, several highlighted issues with sustainability, monitoring, and evaluation. Contribution/value This review provides valuable insights for educators, policymakers, and researchers by offering a synthesized overview of what has been done and what remains to be addressed in the field of school-based literacy initiatives. It underscores the need for more longitudinal studies and context-specific strategies to enhance the effectiveness and sustainability of literacy movements in schools.